Studi Kajian Kandungan Bahan - sujarwo sujarwo; Vita Nur Latif; Ardiana Priharwanti (Pena Medika Jurnal Kesehatan, 2020)
Supervision of food safety in Pekalongan City in 2010-2012 showed that 6.27% of food contained hazardous food additives. Dangerous food additives most often used by the small industry / home food industry is from the type of preservative (Formal and Borax) and types of textile dyes (Rhodamin B and MethanylYellow). According to Permenkes RI No. 33 of 2012, the four chemicals are prohibited from being used in food products because they are harmful to health. The design of this study is a descriptive study in the form of a case study of the results of food safety surveillance activities in Pekalongan City in 2018-2019. The results of this study identified that the types of food most often found to contain food additives, dangerous preservatives (formalin and borax) were yellow noodles; meatball, indil and cilok; terinasi (Teri Medan); and Otak-otak. The types of food that were most often found to contain food additives harmful dyes (Rhodamin B and Methanil yellow) were red krupuk useg; pudding; powdered seasoning; and yellow krupuk useg.Key words: food safety, type of food, dangerous food additives. ABSTRAKPengawasan keamanan pangan di Kota Pekalongan tahun 2010-2012 menunjukan hasil 6,27% pangan mengandung bahan tambahan pangan (BTP) berbahaya. BTP berbahaya paling sering digunakan oleh industri kecil/ industri rumah tangga pangan adalah dari jenis pengawet (Formalindan Boraks) dan jenis pewarna tekstil (Rhodamin B dan MethanylYellow). Menurut Permenkes RI No. 33 Tahun 2012, keempat bahan kimia tersebut dilarang penggunaannya dalam produk pangan karena berbahaya bagi kesehatan. Disain penelitian ini adalah penelitian deskriptif yang berupa studi kasus hasil kegiatan pengawasan keamanan pangan di Kota pekalongan tahun 2018-2019. Hasil  penelitian ini teridentifikasi jenis pangan paling sering diketemukan mengandung BTP berbahaya pengawet (formalin dan boraks) adalah jenis mie kuning; bakso, indil dan cilok; terinasi (teri Medan); dan otak-otak. Jenis pangan paling sering diketemukan mengandung BTP berbahaya pewarna (Rhodamin B dan Methanil yellow) adalah jenis krupuk useg merah; puding; bumbu bubuk; dan krupuk useg kuning.Kata Kuci : keamanan pangan, Jenis pangan, bahan tambahan pangan (BTP) berbahaya